Assess Hydrological Regime Changes in the Upper Da River under the Impacts of Climate Change and Socio-economic Development - Y Nhu, Nguyen; Dinh Kha, Dang; Phuong Linh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1S, 2025)
The Da River, the principal tributary of the Red River system, plays a strategic role in hydropower generation and water supply for northern Vietnam. The hydrological regime of its upper basin has been increasingly influenced by the combined impacts of climate change and transboundary reservoir regulation. This study presents the first integrated assessment of these two factors within a unified SWAT-SUFI-2 modelling framework to evaluate the streamflow alterations in the upper Da River basin. Results indicate that under natural flow conditions without reservoir regulation, climate change intensifies flow extremes, with mean flood-season discharge increasing by approximately 2.5 times, while the number of low-flow months (Q < P₅) during the dry season rises 17 - fold compared with the baseline period (1980 - 2003). In contrast, during the reservoir operation phase (post-2007), the flood peak magnitude decreased by 17.5%, whereas dry-season discharge increased by 11.7%, effectively flattening the seasonal hydrograph. When both factors are considered jointly, reservoirs dominate the redistribution of seasonal flows, and climate change amplifies hydrological variability and extremes. This study provides the first quantitative evidence of the combined impacts of climate change and reservoir regulation on the transboundary Da River basin, offering a scientific basis for adaptive reservoir operation, data sharing, and integrated downstream water-risk management.